2023
DOI: 10.3390/plants12030431
|View full text |Cite
|
Sign up to set email alerts
|

Biostimulation of Petroleum-Contaminated Soil Using Organic and Inorganic Amendments

Abstract: The most common approaches for the in-situ bioremediation of contaminated sites worldwide are bioaugmentation and biostimulation. Biostimulation has often proved more effective for chronically contaminated sites. This study examined the effectiveness of optimized water hyacinth compost in comparison with other organic and inorganic amendments for the remediation of crude oil-polluted soils. Water hyacinth was found to be rich in nutrients necessary to stimulate microbial growth and activity. An organic geochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…Soil pollution with petroleum-derived products causes disorders in soil metabolism [ 116 ], which need to be considered from the perspective of sustainable development [ 100 ], health of soil and plants [ 29 , 33 , 34 , 96 ] and the feasibility of homeostasis restoration in the ecosystem [ 117 , 118 ]. For these reasons, it is essential to determine the activity of soil enzymes in real time when establishing soil quality [ 19 , 75 , 76 , 102 , 119 , 120 ].…”
Section: Discussionmentioning
confidence: 99%
“…Soil pollution with petroleum-derived products causes disorders in soil metabolism [ 116 ], which need to be considered from the perspective of sustainable development [ 100 ], health of soil and plants [ 29 , 33 , 34 , 96 ] and the feasibility of homeostasis restoration in the ecosystem [ 117 , 118 ]. For these reasons, it is essential to determine the activity of soil enzymes in real time when establishing soil quality [ 19 , 75 , 76 , 102 , 119 , 120 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have been conducted on pepper fertilization technology, demonstrating that the application of organic fertilizer, microbial agents, or a combination of reduced chemical fertilizer and organic fertilizer can promote the growth and development of pepper fruits, enhance their quality, and improve overall yield and e ciency (Wen et al 2020; Udume et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, bioaugmentation and biostimulation are the most common techniques worldwide for the bioremediation of petroleum hydrocarbon-contaminated soils performed in situ or ex situ. Bioaugmentation is the intentional supplementation of contaminant-specific degrading microorganisms in contaminated soil to increase the biodegradation rate [ 6 , 7 , 8 ]. Biostimulation involves the addition of nutrients or fertilizers (amendments) to stimulate the growth and the metabolic and degradative activities of microorganisms present in contaminated soils (indigenous microbes) since there is generally a scarcity of nitrogen and phosphorus in the contaminated sites, limiting the availability of these nutrients for the survival of the contaminant-degrading microorganisms [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although bioaugmentation has shown more favorable results than biostimulation, it has also been reported that biostimulation shows better results than bioaugmentation when performed using ideal conditions of temperature, pH, and concentration, among other parameters [ 4 , 8 , 9 ]. Organic and inorganic fertilizers are nutrients used in the biostimulation technique.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation